Understanding Euro Area Inflation Dynamics : Why So Low for So Long? - Abdih, Yasser (IMF Working Papers; Working Paper ;, 2018)
Despite closing output gaps and tightening labor markets, inflation has remained low in the euro area. Based on an augmented Phillips Curve framework, we find that this phenomenon-sometimes attributed to low global inflation-has been primarily caused by a remarkable persistence of inflation, keeping it low despite the reduction in slack. This feature is shown to be specific to the euro area (in comparison with the United States). Monetary policy needs to stay accommodative to help guide inflation back to target.